PMP project management professional - Solomon, Michael 1963- (Pearson, 2010)
PMP Project Management Professional Fourth Edition PMP Exam Cram, Fourth Edition, is the perfect study guide to help you pass the 2009 PMP Exam. It provides coverage and practice questions for every exam topic. The book contains an extensive set of preparation tools such as quizzes and Exam Alerts, while the CD-ROM provides real-time practice and feedback with a 200-question test engine. Covers the critical information you'll need to know to score higher on your exam! . Approach the project management process from PMI's views on project management . Understand the project management framework . Properly initiate projects . Understand the project planning process . Complete the planned project work . Monitor project work and make necessary changes . Close projects . Follow PMI's professional responsibility standards CD Features 200 Practice Questions! The test engine gives you an effective tool to assess your readiness for the exam . Detailed explanations of correct and incorrect answers . Multiple test modes . Random questions and order of answers . Coverage of each PMP exam topic.
Keywords: Project management -- Certification; Project management -- Study guides -- Examinations; Gestion de projet; Examens; Guides de l'étudiant; Project management; Examinations; Study guides